(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Endoresection of uveal melanoma is considered as an alternative treatment for large amounts uveal melanoma or when the application of laser or radiation therapy is limited. The main problem in endoresection remains intraoperative bleeding. Purpose. To study the effectiveness of bimanual endovitreal resection of uveal melanoma using high-frequency electric welding of biological tissues. Material and methods. We observed 4 patients (4 eyes) with a diagnosis of uveal melanoma. In order to devitalisation in all cases performed transpupillary thermotherapy and brachytherapy. After these procedures vitrectomy was performed. We evaluated the presence of hemorrhagic complications during surgery and in the early postoperative period. Results. In all cases the uveal melanoma has been completely removed without intraoperative complications. In all cases, in 4 mm from the limbus we install additional lighting source model Shandelier (25g), which made possible to perform bimanual endoresection of tumor tissues, simultaneously using vitreotom and probe for high-frequency electric welding of biological tissues. Operation There were no significant bleeding complications intraoperatively and in early postop period. In one case local preretinal hemorrhage at the edge surgical chorioretinal coloboma was diagnosed. Conclusion. The proposed technique of bimanual endoresection of uveal melanoma гыштп high-frequency electric welding of biological tissues allow us to avoid intraoperative bleeding complications in all cases.